Differential adenine methylation analysis reveals increased variability in 6mA in the absence of methyl-directed mismatch repair - Carl J. Stone; Gwyneth F. Boyer; Megan G. Behringer (mBio, 2023)
ABSTRACT Methylated DNA adenines (6mA) are a critical epigenetic modification in bacteria that affect cell processes like replication, stress response, and pathogenesis. While much work has been done characterizing the influence of 6mA on specific loci, very few studies have examined the evolutionary dynamics of 6mA over long time scales. We used third-generation sequencing technology to analyze 6mA methylation across the Escherichia coli K-12 substr. MG1655 genome. 6mA levels were consistently high across GATC sites; however, we identified regions where 6mA is decreased, particularly in intergenic regions, especially around the −35 promoter element, and within cryptic prophages and IS elements. We further examined 6mA in WT and methyl-directed mismatch repair-deficient (MMR-) populations after 2,400 generations of experimental evolution. We find that, after evolution, MMR- populations acquire significantly more epimutations resulting in a genome-wide decrease in 6mA methylation. Here, clones from evolved MMR- populations display non-deterministic sets of epimutations, consistent with reduced selection on these modifications. Thus, we show that characterization of 6mA in bacterial populations is complementary to genetic sequencing and informative for molecular evolution. IMPORTANCE Methylation greatly influences the bacterial genome by guiding DNA repair and regulating pathogenic and stress-response phenotypes. But, the rate of epigenetic changes and their consequences on molecular phenotypes are underexplored. Through a detailed characterization of genome-wide adenine methylation in a commonly used laboratory strain of Escherichia coli, we reveal that mismatch repair deficient populations experience an increase in epimutations resulting in a genome-wide reduction of 6mA methylation in a manner consistent with genetic drift. Our findings highlight how methylation patterns evolve and the constraints on epigenetic evolution due to post-replicative DNA repair, contributing to a deeper understanding of bacterial genome evolution and how epimutations may introduce semi-permanent variation that can influence adaptation.